2015
DOI: 10.1016/j.jcis.2014.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Release of small hydrophilic molecules from polyelectrolyte capsules: Effect of the wall thickness

Abstract: Polymer nanocapsules assembled on cationic liposomes have been built through the layer-by-layer (LbL) technique. Chitosan and alginate, two biocompatible polyelectrolytes, were used to cover the template, where the Rhodamine B was previously loaded. The multishell formed with the alternate deposition of the polyelectrolytes, according to the principles of the LbL assembly, was supposed to change the permeability of the capsule wall. The thickness of the multishell was seen increasing with the number of layers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…Up to now, the methods usually employed for liposome covering by chitosan are based essentially on dropwise bulk methods 13,18,[24][25][26][27][28][29] such as the layer-bylayer (LbL) method. 30,31 Some efforts have been made towards improvement of these conventional methods using, for example, a supercritical reverse-phase evaporation method, 32 by exploiting complex and expensive apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the methods usually employed for liposome covering by chitosan are based essentially on dropwise bulk methods 13,18,[24][25][26][27][28][29] such as the layer-bylayer (LbL) method. 30,31 Some efforts have been made towards improvement of these conventional methods using, for example, a supercritical reverse-phase evaporation method, 32 by exploiting complex and expensive apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…Cuomo and coworkers reported that low or high molecular weight molecules were released with a non-Fickian type of transport from polyelectrolyte capsules made of alginate and chitosan. The release rate decreased, while the molecular weight and the multishell thickness increased [42,43] (Figure 2).…”
Section: Molecular Diffusion Through Polymeric Capsulesmentioning
confidence: 98%
“…Multilayer film PLL c /liposomes/PMAc/PVP/PMA SH [19,82] Alginate/Chitosan Multilayer film ALG/CHI [7,22,42,43] Poly(sodium-styrene sulfonate)/poly(allylamine) hydrochloride Multilayer film PSS/PAH [5] Glucose oxidase/Catalase Multilayer film GOX/CAT [79] Glucose oxidase/polyethylenimine/Catalase Multilayer film GOX/PEI/CAT [80]…”
Section: Membrane Composition Reference Polymer Name Acronymmentioning
confidence: 99%
See 1 more Smart Citation
“…In the classical book of Crank [5], the diffusion in a sphere from a well-stirred medium is solved by Fourier expansion in the case of constant or time varying surface concentration and the case of a constant flux at the surface. More recent work includes empirical, semi-empirical and mechanistic diffusion models [9]. An exact solution for diffusional release of a dispersed solute from a spherical polymer matrix into both semi-infinite and finite external mediums has been developed [10,11].…”
Section: Introductionmentioning
confidence: 99%